Synthesis of Heterocycles from Donor-Acceptor Cyclopropanes: A Five-Year Recap - Deepthi, Ani; B., Meenakshy C.; Mohan, Maneesh (Synthesis, 2023)
This review discusses the utility of donor-acceptor cyclopropanes (DACs) for the construction of heterocycles. In addition to (3+2), (3+3), and (4+3) cycloaddition pathways, nucleophilic ring-opening reactions, intramolecular transformations, and cycloisomerizations in the presence of suitable catalysts pave the way for the generation of heterocycles from DACs. The mild reactions conditions employed and the variety of starting materials that can be used as reaction partners make the DAC route for heterocycle synthesis attractive. The literature covered in this review is from the period 2018 to 2023.1 Introduction2 Synthesis of Nitrogen Heterocycles2.1 By Annulations with Anthranils and Azadienes2.2 By Nucleophilic Attack of Anilines and Hydrazones2.3 By Reaction with Ureas and Thioureas2.4 By Annulation Reactions Using an Azomethine Imine2.5 By Reaction with Other Nitrogen Heterocycles2.6 By Other Transformations3 Synthesis of Oxygen Heterocycles3.1 By Intramolecular Transformations3.2 By Intermolecular Reactions4 Synthesis of Sulfur and Selenium Heterocycles4.1 By Reaction with Thiocarbonyl Substrates4.2 By Reaction with Thio- and Selenocyanates and Thiosulfonate Salts5 Synthesis of N–S and N–O Heterocycles6 Conclusions
Keywords: donor-acceptor cyclopropanes; heterocycles; annulation; nucleophile; ring-opening